Maximizing performance through performance management system : a case study in an organization in the banking industry - Abdul Rahman, Mariam (1999)
Performance measurement is about measuring contribution of employees; it is the process of seeking to establish the output of staff performance against the rewards. Organisations need to have a proper measurement of performance management as it is crucial to any incentive pay plan of the entire company. Employees need performance management as it helps them to learn what they need to do or do differently in order to meet their set targets and meeting the organisations objective for them to reap the benefits individually, as a team or as an organisation. The success of the performance management in an organisation will depend on all the people involve in the process; the type of performance management system chosen, the implementation process and the rewards and recognition attach to the system will determine the motivational factors in the organisation not mentioning the ignition factor for any grievances, low morale and pushing factor for staff to look for greener pasture. The study was carried out to review the efforts taken by an organisation in coming out with a new improve performance management system. The need for the change, the processes taken in identifying the new system as well as to study the feature of the new system in an effort to maximise staff performance was revealed.